A multistimuli‐responsive supramolecular polymer constructed by crown ether‐based molecular recognition and disulfide bond connection. Issue 18 (27th May 2015) - Wang, Hu; Wang, Pi; Xing, Hao; Li, Ning; Ji, Xiaofan
<x xml:space="preserve">Abstract</x> We report a novel multistimuli‐responsive supramolecular polymer constructed by a bis(benzo‐21‐crown‐7)‐based AA monomer containing a disulfide bond and a bis(dialkylammonium salt)‐based BB monomer. Interestingly, the responsivenesses of this supramolecular polymer is not only from the stimuli‐responsive noncovalent interactions but also from the stimuli‐responsive disulfide bond.